Smart home with house module: overview of automation technologies - Polikanov, К.; Sotnik, S. (My University, 2024)
The work discusses main automation technologies used in concept of "smart home" on Modular House platform. The advantages of modular approach to construction and integration of automation systems, including IoT, automated systems for climate control, security and energy management, are described. The features of increasing comfort due to such solutions, as well as issues regarding safety and energy efficiency of housing, providing users with opportunity to flexibly manage their environment, are determined. Attention is paid to prospects for development of similar technologies in future.
Keywords: smart home; house module; automation; climate control